Strategi Pengembangan Ekowisata Masyarakat Desa Komodo, Kecamatan Komodo, Manggarai Barat, Nusa Tenggara Timur - Muchlashin, Anif (UNIVERSITAS ISLAM SYEKH YUSUF, 2023)
The focus of this research explores the empowerment activities carried out in the Komodo Tourism Village area, Komodo District, West Manggarai Regency, East Nusa Tenggara Province. Researchers found a problem, namely the lack of knowledge in the Komodo Tourism Village community. Komodo Tourism Village is one of the strategic places for tourists to meet Komodo dragons directly in a lying nature, this can be interpreted that the natural resources in Komodo Village are one of the strategic places to be upgraded to become a more visited Tourism Village area traveler. Researchers used the PAR (Participatory Action Research) methodology as a research method. The systematics of PAR are to know, to understand, to plan and to act. The PAR methodology is directed at community empowerment, namely efforts to create community self-reliance. Through the research approach used, it is known that the root of the problem is the lack of community capacity in processing natural resources and tourism in the Komodo area. Through this empowerment activity capacity building has been carried out by strengthening Pokdarwis institutions, forming guide lines, socializing and empowering MSMEs, taking videos in the framework of promoting cultural attractions and tourism promotion, and bazaar parties and people's promos (pespora).